Impact of halal knowledge on halal awareness through @halalcorner's role: a PLS-MGA (Partial Least Square- Multi Group Analysis) - Safitri, Lensa Rosdiana; Syukriya, Alvi Jauharotus; Maulida, Utik (Journal of Halal Product and Research (JHPR), 2024)
In today's digital era, social media, especially Instagram, has become a influential platform for disseminating information and shaping individual attitudes and behaviors. The Instagram account @HalalCorner focuses on information and education related to halal awareness. This account presents various content related to halal products, halal certification processes, product reviews, as well as the latest news and information about halal. This research aims to explore the role of the @HalalCorner Instagram account in strengthening the influence of knowledge about halal on increasing halal awareness among the public. The research employs a quantitative approach with survey techniques and questionnaires distributed to 29 followers and 69 non-followers. The variables examined include knowledge and awareness of halal. The statistical method used for hypothesis testing is Partial Least Square Multi Group Analysis (PLS MGA). This research is expected to provide insights into the potential use of social media in enhancing halal awareness and lay the groundwork for further interventions in leveraging digital platforms for educational purposes related to halal awareness. Keywords: Halal Awareness, Halal Knowledge, Halal Corner